Resistance to Whitebacked Planthopper in Elite Lines of Cultivated x Wild Rice Crosses - Ye, Z.H.; Saxena, R.C. (Wiley, 1990)
Wide hybridization is an important breeding tool for incorporating alien genetic variation and transfer of useful traits from wild species of Oryza to commercial rice (‘O. sativa’ L.) cultivars. Wevaluated two elite lines, ‘IR54742‐23‐1‐29‐18’ (hereafter called IR54742) and ‘IR54751‐2‐41‐10‐5’ (hereafter called IR54751), selected from 243 lines derived from BC2F6 progenies of crosses between cultivated rice and wild rice (O. officinalis Wall) for resistance to the whitebacked planthopper Sogatella furcifera (Horvàth). The insect's behavioral and physiological responses were tested on the two elite lines and their parents ‘IR31917‐45‐3‐2’ (hereafter called IR31917) and wild rice. ‘IR2035‐117‐3’ (hereafter called IR2035) was the resistant check, while ‘Taichung Native 1’ (TN1) was the susceptible check. Insect food intake and assimilation, growth, longevity and fecundity, and population increase were least on wild rice. The level of insect resistance of IR54751 was comparable to that of IR2035, but insect growth was significantly more on IR54751. IR54742 was comparably less resistant than IR54751. There was no significant difference in insect responses to IR31917 and TNI. The interspecific transfer of gene(s) for planthopper resistance from wild rice to cultivated rice was confirmed.